The Impact of ICT on Education - Anastasopoulou, Eleni; Angeliki Tsagri; Eleni Avramidi; Konstantina Lourida; Evangelia Mitroyanni; Danai Tsogka; Ioannis Katsikis (Technium Social Sciences Journal, 2024)
The integration of Information and Communication Technology (ICT) into education has fundamentally transformed teaching and learning processes, offering new avenues for enhancing educational experiences and outcomes. This paper explores the multifaceted impact of ICT on education, focusing on its ability to provide unprecedented access to information, foster innovative teaching methodologies, increase student engagement, and promote educational equity. By leveraging digital tools and resources, educators can create dynamic and interactive learning environments that cater to diverse learning styles and needs. ICT also empowers students to engage in self-directed learning and collaborate with peers across geographical boundaries. Moreover, the implementation of assistive technologies and adaptive learning platforms ensures that students with disabilities receive tailored support, promoting inclusivity. The potential of ICT to bridge educational gaps in underserved regions by providing high-quality content and flexible learning options underscores its role in advancing educational equity. Despite challenges such as the digital divide, the continued investment in ICT infrastructure and the adoption of innovative educational practices can create a more inclusive and equitable educational ecosystem. Ultimately, ICT holds the promise of reshaping the educational landscape, preparing students for success in the digital age and beyond.